The Nefroprotector Effect of Salam Leaf Extract (Syzygium polyanthum) in Miceâs Renal Cell which is Induced by Paracetamol - Faras, Asaduddien; S, Endang Listyaningsih; Setyawan, Sigit (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : Salam Leaf (Syzygium polyanthum) contains antioxidants such as flavonoids, selenium, vitamin A, vitamin C, vitamin E, triterpenes, tannins, saponins, niacin, and essential oils as an antioxidant compounds. In present study, Syzygium polyanthum leaves extract was evaluated for its protective effect on paracetamol- induced renal damage in mice. Methods: This study was laboratory experimental research with Randomized Controlled Trial design. A total of 28 Swiss Webster mices were equally divided into 4 groups. Mices for control group (KK) and the first group (KP1) will be given aquadesÂ for 14 day. The second(KP2) and third (KP3) group will be given Salam leaf extract with dose 7 mg/20 g and 14 mg/20 g weight of mice for 14 days. While paracetamol in toxic dose was given on to KP1, KP2, KP3, with dose 0,1 ml/ 20 g weight of mice on day 12, 13 and 14. Mice were sacrificed with neck dislocation on the 15th day and histological preparation was made to evaluate histological damage on proximal tubular renal cells stained by Hematoxillin Eosin (HE). Renal histological features were assesed by counting the number of proximal tubular renal cells histogical damage. Data were analyzed by One-Way ANOVA test (Î± = 0,05) continued by Post Hoc Multiple Comparisons test (LSD)(Î± = 0,05). Results: The results of One-Way ANOVA test showed p < 0.05 that there was significant difference between four-groups. LSD test results showed p < 0,05 there was significant differenceÂ between grups. Conclusion: Salam leaf extract can prevent the renal cell damage of mice. The difference dose of salam leaf extract give different effects nefroprotector in miceâs renal cell. Keywords : salam leaf extract, paracetamol, renal histologic structure damage